ON ONE OF THE REASONS OF THE INSTABILITY OF THE SOLUTIONS IN APPLYING COMPUTATIONAL METHODS IN MECHANICS - M. S. Kublanov (Научный вестник МГТУ ГА)
The article provides an overview of cases of stiffness, leading to inadequate results of mathematical models of mechanics. An attempt is made to generalize look at this phenomenon for body dynamics, and for the continuum mechanics. Proposed wording of display of stiffness properties of the mechanical systems, the primary cause of unstable solutions and makes recommendations for the development of sustainable calculation metods.